PENINGKATAN HASIL BELAJAR PENYAJIAN DATA MELALUI MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS VB SD NEGERI KRASAK 01 BREBES - Nur Indah Syafiqoh; Mei Fita Asri Untari; Ulin Nafiah (JS (JURNAL SEKOLAH), 2021)
Abstract : Improving Data Presentation Learning Outcomes through Problem Based Learning (PBL) Models for Class VB Students at SD Negeri Krasak 01 Brebes. This study aims to determine the improvement of mathematics learning outcomes through the Problem Based Learning (PBL) learning model in class VB SD Negeri Krasak 01 Brebes in the academic year 2020/2021. This type of research is classroom action research (CAR) which is carried out in three cycles. The research was conducted at SD Negeri Krasak 01 Brebes. The research subjects were 34 students of class VB, consisting of 17 male students and 17 female students. Data collection techniques used are interviews, observation, documentation, and learning outcomes tests. Furthermore, the collected data were analyzed using descriptive qualitative and quantitative descriptive methods. The results of data analysis showed that student learning outcomes (cognitive aspects) showed an increase from the first cycle, namely students completed as much as 70.6% with an average of 71.0 cycle II students completed 82.3% with an average of 78.9 until the second cycle. III students completed by 88.2% with an average of 83.6. Based on data analysis, research results, and discussion, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve Mathematics learning outcomes for class VB at SD Negeri Krasak 01 Brebes for the 2020/2021 academic year.Keywords: Problem Based Learning (PBL) Model, Learning Outcomes, Mathematics.Abstrak : Peningkatan Hasil Belajar Penyajian Data melalui Model ProblemBased Learning (PBL) pada Siswa Kelas VB SD Negeri Krasak 01 BrebesPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar matematika melalui model pembelajaran Problem Based Learning (PBL) pada siswa kelas VB SD Negeri Krasak 01 Brebes Tahun Pelajaran 2020/ 2021. Jenis penelitian ini adalah penelitian tindakan kelas (PTK) yang dilaksanakan dalam tiga siklus. Penelitian dilakukan di SD Negeri Krasak 01 Brebes. Subjek penelitian adalah siswa kelas VB yang berjumlah 34 siswa, yang terdiri atas 17 siswa laki-laki dan 17 siswa perempuan. Teknik pengumpulan data yang digunakan yaitu wawancara, observasi, dokumentasi, dan tes hasil belajar. Selanjutnya data yang terkumpul dianalisis dengan menggunakan metode deskriptif kualitatif dan deskriptif kuantitatif. Hasil analisis data menunjukkan bahwa hasil belajar siswa (aspek kognitif) menunjukkan peningkatan dari siklus I yaitu siswa tuntas sebanyak 70,6% dengan rata- rata 71,0 siklus II siswa tuntas sebesar 82,3% dengan rata-rata 78,9 sampai siklus III siswa tuntas sebesar 88,2% dengan rata-rata 83,6. Berdasarkan analisis data, hasil penelitian, dan pembahasan dapat disimpulkan bahwa penerapan model pembelajaran Problem Based Learning (PBL) dapat meningkatkan hasil belajar Matematika kelas VB SD Negeri Krasak 01 Brebes Tahun Pelajaran 2020/2021.Kata Kunci: Model Problem Based Learning (PBL), Hasil Belajar, Matematika